DO PERUVIAN MIGRANTS CONTRIBUTE TO THE COUNTRY'S EXPORTS? - Hennings Otoya, Julio Alberto (2010)
This article seeks to answer the question whether Peruvian migrants, whose number would exceed 10% of the population living in the homeland, has contributed in some way with the development of national exports, considering that comprise a consumer segment with its own characteristics, habits and preferences related to their homeland. The last fact, combined with factors such as improved purchasing power of those who have emigrated to developed countries, the variety of resources considered national origin or “ethnic” fame and the boom that is taking the peruvian cuisine and other national attractions would be generating a market opportunity for many entities in production, trade and tourism in the country. After a process of analysis of studies relating to the subject, confronted with the reality applied in our environment, are generated the conclusions and recommendations, which could be exploited by Peruvian companies seeking to develop their potential in the international market, making it also stressed that the deepening of the subject could provide a framework for policies and actions of State, to integrate Peruvian migrants in Peru’s development strategies.